Filling the evidence void: exploration of coach and healthcare provider experiences working with pregnant and postpartum elite athletes - a qualitative study - Davenport, M. H.; Ray, L.; Nesdoly, A.; Thornton, J. S.; Khurana, R.; McHugh, T.-L. F. (British Journal of Sports Medicine, 2023)
Objective Recent research grounded in the experiences of elite female athletes has shed light on the complex challenges of navigating sport environments that do not support or value pregnant or postpartum athletes. The purpose of this study was to explore the unique experiences of coaches and healthcare providers working with pregnant and postpartum elite athletes, and to identify actionable steps for research, policy and culture change to support them.